SUBORDINATOR RELASI TEMPORAL DALAM KALIMAT MAJEMUK BERTINGKAT - Prabawa, Andi Haris (Kajian Linguistik dan Sastra, 2007)
The study describes subordinators indicating temporal relations of equivalenceand sequence in which their existence in compound-complex sentences are obligatory.The distribution method and its five techniques (Immediate Constituent, deletion,permutation, substitution, and expansion) are used to identify the types anddistribution of the subordinators within the Indonesian sentences. The result showsthat subordinators indicating equivalence of temporal relations are saat, ketika,waktu, sewaktu, kala, tatkala, selama, and selagi. Meanwhile, subordinators indicatingsequence of temporal relations are begitu, usai, sesuai, sesudah, selepas, andsehabis. The distribution of the two kinds of subordinators in the cimpound-complexsentences vary; they can be placed initially, medially after the main clause,and after subject of the main clause.